Transplantation of ectopic upper canine into its proper position on the jaw: a case report - Tammama, Tichvy; Kurniawan, Irsan; Maqdisa, Siti Risa; Banerjee, Abhishek (Jurnal Kedokteran Gigi Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: Tooth transplantation is the transfer of one tooth into its new position in the jaw of the same person. The purpose of this case report is to discuss the transplantation of an ectopic upper canine to the proper position where the primary canine is still occupied. Case report: a female patient came to the Oral Surgery clinic with a complaint that her left upper canine was growing towards the palate, so that her deciduous teeth did not fall out. The treatment for this patient was the atraumatic extraction of the left deciduous canine teeth and the permanent canine, then the permanent canine was transplanted into a socket of the deciduous teeth that was extracted. The transplanted= canines were then fixed with interdental wiring (IDW) for 3 months. At the time of follow-up, the canine was healing well, and was able to work well. A tooth can be transplanted into its new position with the best achieved if the integrity of the periodontal membrane remains vital, the extraction process is as atraumatic as possible, and with a short time of the tooth was outside the mouth. Conclusion: an ectopic tooth can be transplanted in proper position in the arch if there is sufficient space, the integrity of the periodontal ligament is maintained, time outside the mouth is short, and accompanied by adequate fixation. Key words: ectopic, interdental wiring (IDW), canine, transplantationTransplantasi kaninus rahang atas yang mengalami ektopik pada lokasi yang seharusnya di rahang: laporan kasusABSTRAKPendahuluan: Transplantasi gigi yaitu pemindahan satu gigi ke tempat baru pada rahang orang yang sama. Tujuan dari laporan kasus ini yaitu membahas mengenai transplantasi kaninus atas yang ektopik ke posisi seharusnya yang masih ditempati oleh kaninus sulung. Laporan kasus: pasien wanita datang ke poli Bedah Mulut dengan keluhan gigi kaninus atas kiri tumbuh ke arah langit-langit, sehingga gigi kaninus sulungnya tidak lepas. Perawatan pada pasien ini yaitu dilakukan pencabutan gigi kaninus sulung dan gigi tetap kaninus tersebut secara atraumatik, kemudian gigi kaninus tetapnya ditransplantasikan pada soket bekas gigi kaninus sulung yang dicabut tersebut. Gigi kaninus yang ditransplantasi kemudian difiksasi dengan interdental wiring (IDW) selama 3 bulan. Saat kontrol, gigi kaninus telah mengalami penyembuhan dengan baik serta dapat berfungsi baik. Suatu gigi dapat ditransplantasikan ke posisi yang baru, jika integritas membran periodontal terjaga vitalitasnya, proses ekstraksi sea traumatik mungkin, dan gigi berada di luar mulut sesingkat mungkin. Simpulan: Gigi yang ektopik dapat dilakukan transplantasi ke posisi yang seharusnya pada lengkung rahang apabila terdapat ruang yang cukup, integritas ligamen periodontal tetap terjaga, waktu di luar mulut singkat, serta fiksasi yang adekuat.Kata kunci: ektopik, interdental wiring (IDW), kaninus, transplantasi